타 교과에서 나타나는 그래프의 특징 분석 및 예비 수학교사들의 인식 조사 - 지구과학 교과를 중심으로 - 김래용; Rae Yong Kim; 박진우; Jin-woo Park (과학교육연구지, 2024)
본 연구는 예비 수학교사들의 타 교과에서 제시된 그래프에 대한 인식을 분석하는 목적으로 수행되었다. 이를 위해 2015년 개정 교육과정에 의해 집필된 지구과학 I 교과서에 제시된 시각 자료들을 전문가 분석을 바탕으로 [그래프에 대한 인식 설문]을 구성하고, 경북 소재의 D대학에 재학 중인 2학년과 3학년 예비 수학교사 각각 10명을 대상으로 선택하여 개발된 설문 도구를 바탕으로 그래프에 대한 인식을 조사하였다. 이에 대한 결과는 다음과 같다. 첫째, 지구과학 교과서에서 제시되는 그래프는 그래프에 대한 수학적 정의와는 다소 차이가 있는 유형으로 표시되는 경우가 다수 확인되었고, 이에 대해 지구과학 전문가의 의견도 나뉘는 것으로 확인되었다. 둘째, 예비 수학교사들의 그래프에 대한 인식은 수학 전문가들과 거의 일치하나, 그 적용이 상대적으로 유연하지 못함을 확인하였다. 융합교육의 중요성이 강조되고 있는 상황에서 다른 학문 영역에서 다루어지는 요소들의 모호성을 제거할 수 있는 후속 연구가 필요하며, 이를 통해 융합 교육의 발전과 학생들의 이해도 및 성취도를 높일 수 있길 기대한다. In this study, we analyze the perception of graphs appeared in other subjects by prospective mathematics teachers. To this end, we construct the survey [Graph Perception Survey] based on the visual materials presented in the Earth Science I textbook written by the 2015 revised curriculum, select 10 second- and third-year prospective teachers enrolled in D University in Gyeongbuk Province and investigate their perceptions of graphs. The results are as follows: First, it was found that graphs appeared in earth science textbooks are often displayed in a type that is somewhat different from the mathematical definition of graphs, and the opinions of earth science experts are not consistent. Second, it was found that the perception of graphs of prospective mathematics teachers almost agree to that of mathematics experts, but their application is relatively inflexible. We hope that this research will lead to the development of convergence education and to improve students' understanding and achievement.